Seaworthy volumes [2] - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The living marine resources of the Western Central Pacific, Vol. 6 Bony fishes part 4. (Labridade to Latinmeriidae), estuarine crocodiles, sea turtles, sea snakes and marine mammals, FAO, 2001. 844 pp.